2008
DOI: 10.1007/s10551-008-9669-4
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Link Between Corporate Social Responsibility and Consumer Trust: The Case of Fair Trade Products

Abstract: This paper investigates the link between the\ud consumer perception that a company is socially oriented\ud and the consumer intention to buy products marketed by\ud that company. We suggest that this link exists when at least\ud two conditions prevail: (1) the products sold by that company\ud comply with ethical and social requirements; (2) the\ud company has an acknowledged commitment to protect\ud consumer rights and interests. To test these hypotheses, we\ud conducted a survey among the clients of retail ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
345
0
32

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 503 publications
(417 citation statements)
references
References 53 publications
15
345
0
32
Order By: Relevance
“…Several scholars observed that stakeholders tend to favor relationships with companies that are more aligned to their expectations. For example, CSR practices tend to increase customers' trust (Castaldo et al, 2009); responsible consumers are willing to pay a premium price for more sustainable products (Brown and Dacin, 1997); employees are attracted and motivated by companies that are environmentally and socially conscious (Brammer et al, 2007); policy makers may reduce their regulatory, legislative, or fiscal pressures for responsible companies (Hillman and Keim, 2001); and sustainable firms can attract financial investors (Doh et al, 2010). The benefits for firms are expected to depend on the capacity to respond to and influence stakeholders (Barnett, 2007).…”
Section: Environmental Performance: Process Versus Outcomementioning
confidence: 99%
“…Several scholars observed that stakeholders tend to favor relationships with companies that are more aligned to their expectations. For example, CSR practices tend to increase customers' trust (Castaldo et al, 2009); responsible consumers are willing to pay a premium price for more sustainable products (Brown and Dacin, 1997); employees are attracted and motivated by companies that are environmentally and socially conscious (Brammer et al, 2007); policy makers may reduce their regulatory, legislative, or fiscal pressures for responsible companies (Hillman and Keim, 2001); and sustainable firms can attract financial investors (Doh et al, 2010). The benefits for firms are expected to depend on the capacity to respond to and influence stakeholders (Barnett, 2007).…”
Section: Environmental Performance: Process Versus Outcomementioning
confidence: 99%
“…Existing research provides a number of ways in which CSR activities enhance relationships with consumers, such as increased trust and loyalty towards retailers (Castaldo et al 2009), as well as a disposition to pay higher prices for products (Laroche et al 2001;De Pelsmacker et al 2005). Additional outcomes include greater purchase intentions (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The value of CSR can add to the brand, 2) the ability to strengthen the association with accomplices whose support is fundamental to brand quality, and 3) the ability to make the message more persuading and, in this way, to lessening distrust (Bronn and Vrioni, 2001). On the other hand, furthermore unmistakable results were found concerning the impact of an association's CSR attempts on purchase conduct (Castaldo et al, 2009). In the examination of Mohr et al (2001) for instance customers ensure that they are willing to pay higher expenses for the consequences of associations which possessed with CSR.…”
Section: Theoretical Modelmentioning
confidence: 99%